2015
DOI: 10.1007/s13402-014-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial induction as a potential radio-sensitizer in lung cancer cells - a short report

Abstract: Mitochondrial induction by DCA may serve as a radio-sensitizer in non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Based on these results, we performed all remaining studies with A549 and H1299 lung adenocarcinoma cells with 50 mM DCA. A very recent study by Shavit et al in 2015 has confirmed similar IC 50 values in vitro for both A549 and H1299 cells [31].…”
Section: Dca Alters Lactate Production and Glucose Consumption In A54mentioning
confidence: 69%
See 2 more Smart Citations
“…Based on these results, we performed all remaining studies with A549 and H1299 lung adenocarcinoma cells with 50 mM DCA. A very recent study by Shavit et al in 2015 has confirmed similar IC 50 values in vitro for both A549 and H1299 cells [31].…”
Section: Dca Alters Lactate Production and Glucose Consumption In A54mentioning
confidence: 69%
“…Some studies indicate that targeting cancer cell Warburg metabolism with metabolic agents has therapeutic potential especially in combination with radiation or chemotherapy [14][15][16][17][18][19]31]. DCA is a synthetic small molecule that has high bioavailability and is currently being used to treat hereditary metabolic or cardiovascular diseases [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichloroacetate, a PDK inhibitor that has the potential for such metabolic targeting, has been shown to reverse the Warburg effect by shifting glucose metabolism from glycolysis to mitochondrial oxidation and to inhibit tumor cell growth (9,10). By combining with radiotherapy, dichloroacetate has been demonstrated to enhance the radiosensitivity of several tumor types in vitro (11)(12)(13). Interestingly, a previous study using 2 human cancer cell lines (colon adenocarcinoma and glioblastoma) demonstrated that dichloroacetate sensitized the efficacy of radiotherapy in vitro but attenuated radiotherapy-induced tumor growth delay in vivo (colon adenocarcinoma model; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is mediated by either an extrinsic pathway, triggered by extracellular stimuli, or by an intrinsic pathway, activated by intracellular modulators [20][21][22][23]. Mitochondria play a critical role in the intrinsic pathway by releasing a series of molecules, including cytochrome c. Within the cytosol, the binding of cytochrome c to adaptor protein Apaf-1 and pro-caspasse-9 molecules leads to the formation of the apoptosome that is responsible for activation of a caspase-dependent apoptotic pathway [24].…”
Section: Introductionmentioning
confidence: 99%